2022
DOI: 10.26434/chemrxiv-2022-78t5s
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Degradable Polystyrene via the Cleavable Comonomer Approach

Abstract: Polystyrene (PS) is a major commodity polymer, widely used in various applications ranging from packaging to insulation thanks to its low cost, high stiffness and transparency as well as its relatively high softening temper-ature. Similarly to all polymers prepared by radical polymerization, PS is constituted of a C-C backbone and thus is not degradable. To confer degradability to such materials, the copolymerization of vinyl monomers with cyclic monomer that could undergo radical ring-opening is an efficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
40
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(42 citation statements)
references
References 31 publications
2
40
0
Order By: Relevance
“…who showed degradation of a crosslinked polystyrene with 5 mol% DOT and 1 mol% of crosslinker, 38 as well as a 3D-printed poly(pentaerythritol triacrylate)-based resin at even lower DOT loading, i.e., 2 wt% (corresponding to 3.1 mol%). 39 We note however, that homopolymerization of a multivinyl monomer will inevitably lead to a large extent of intramolecular cyclization reactions.…”
Section: Scheme 1 Synthesis Of Pba-dot Network By Frp and Their Degra...mentioning
confidence: 99%
See 2 more Smart Citations
“…who showed degradation of a crosslinked polystyrene with 5 mol% DOT and 1 mol% of crosslinker, 38 as well as a 3D-printed poly(pentaerythritol triacrylate)-based resin at even lower DOT loading, i.e., 2 wt% (corresponding to 3.1 mol%). 39 We note however, that homopolymerization of a multivinyl monomer will inevitably lead to a large extent of intramolecular cyclization reactions.…”
Section: Scheme 1 Synthesis Of Pba-dot Network By Frp and Their Degra...mentioning
confidence: 99%
“…[27][28][29][30][31] Thionolactones, such as dibenzo[c,e]oxepane-5-thione (DOT) have been recently presented as a degradable comonomer which undergo RROP with acrylates, acrylamides, acrylonitrile, [32][33][34][35] as well as vinyl esters, 36 styrene and methacrylates. 37,38 DOT is compatible with both FRP and RDRP and affords degradation via cleavage of the backbone thioester. Very recently, Guillaneuf et al used DOT in crosslinked systems and reported that a 3D-printed poly(pentaerythritol triacrylate) 39 and a poly(styrene-co-divinylbenzene) 38 both underwent degradation with 2 wt% and 5 mol% of DOT, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29][30][31] Thionolactones, such as dibenzo[c,e]oxepane-5-thione (DOT) have been recently presented as a degradable comonomer which undergo RROP with acrylates, acrylamides, acrylonitrile, [32][33][34][35] as well as vinyl esters, 36 styrene and methacrylates. 37,38 DOT is compatible with both FRP and RDRP and affords degradation via cleavage of the backbone thioester by e.g. primary amines, strong bases or thiols.…”
mentioning
confidence: 99%
“…primary amines, strong bases or thiols. Very recently, Guillaneuf et al used DOT in crosslinked systems and reported that a 3D-printed poly(pentaerythritol triacrylate) 39 and a poly(styrene-co-divinylbenzene) 38 both underwent degradation with 2 wt% and 5 mol% of DOT, respectively.…”
mentioning
confidence: 99%